To what extent a sustainable supply chain could be built through relationship approach - Zhou, Ming (2014)
Purpose- Increasingly, companies are aiming to buy and supply products and services sustainably. Therefore, building a sustainable supply chain (SSC) management system is very important for current supply chain management. However, in reality, current method of building SSC is challenged in many ways. A new method of approaching supply chain sustainability should be proposed. Relationship approach is proposed under such situation. However, a buying company is with different relationship towards its suppliers, and so is supplier. The relationship between different types of buyer and supplier indicate different chances of ensure supply chain sustainability. This paper is aiming to firstly, propose a new method to build SSC; secondly, evaluate the chances of building SSC between buyer and supplier.